Achieving Agile Leadership in Digital Era Study Case at State of Defense University - Oryza Tannar; Indrawati Yuhertiana; Partoyo (Nusantara Science and Technology Proceedings, 2022)
This research problem is triggered by changes occurring in various fields caused by technology, health, and the environment. Many companies are forced to suffer losses and even close because they cannot keep up with the changes. The organization slowed down and was eventually abandoned. Therefore, it takes a leader who is agile as well as quick to respond to make decisions immediately. The long-term goal of this research is to build organizational resilience through agile leadership which is the key to saving the organization in times of crisis. The specific target to be achieved is to form a model for staff development at 3 universities in Indonesia that have the same character as state defense campuses, namely UPN “Veteran” Jakarta, UPN “Veteran” Yogyakarta, and UPN “Veteran” Jawa Timur. The method used is a sequential mixed method approach. This study aims to examine the effect of early work education (induction training) and the character of defending the country through employee engagement in agile leadership in the first year. In the second year, this research conducts an in-depth elaboration of employee-engagemen. The output target of this research is published in reputable international journals which in the first year are planned to be published in journals. The TKT of this research is to develop the model so that it is at level 2-3. This research is in accordance with RIRN with the theme of digital economy and also contributes to supporting the achievement of KPI because it involves students, IKU because it involves outside researchers and IKU because the output is a reputable international journal.